Financial Ratio to Financing in Indonesia Islamic Rural Bank Analysis - Muthi' 'Adilah Bahril; Ryan Rahma Maulayati (Department of Islamic Economics, Islamic University of Indonesia, 2020)
The purpose of this study is to analyze factors which influence financing in Indonesia Islamic Rural Bank. The data used are monthly financial report of Islamic Rural Bank (IRB) from 2014 to 2018. This study is using Vector Error Correction Model (VECM) to find the short and long term impacts and respons to the shock impact in each variable to financing. The results respresent that CAR, FDR, BOPO and DPK variables have a significant positive effect on financing in short term. Subsequently in the long term, CAR and NPF variables have a significant positive effect on financing. Meanwhile FDR and DPK variables have a significant negative effect on financing and the ROA variable has no significant effect on financing. Then, the financing response to shocks that occur in ROA, FDR and DPK is negative. While the financing response to shocks that occur in CAR is negative.